(untitled) (Swiss Medical Weekly, 2021)
WHAT IS KNOWN ON THE SUBJECT: Good practice and knowledge in terms of contraception at first sexual intercourse may lead adolescents to a safer sexual life. To date, research studies have mostly focused on women when investigating contraception use or on condom use only when addressing both genders. WHAT DOES THIS ARTICLE ADD: The present study adds to the current knowledge by offering a more in-depth view of contraception use at first intercourse among youths. This is achieved through a large selection of variables, the fact that we address both males and females and that we have considered a wide range of contraceptive means. AIM OF THE STUDY To determine the rate of contraception use at first intercourse by youth in Switzerland and its association with social and personal characteristics. METHODS Data were obtained from a self-administrated national survey on sexual behaviour among young adults (mean age 26 years). Participants (n = 4036) were divided into three groups based on the means of contraception used at first intercourse: condom, with or without contraceptive (86.4%), contraceptive only (8.3%) and non-use (5.3%). RESULTS Only 5.3% did not use any contraception. Compared with the condom group, individuals in the non-use group were more likely to report a lower family socioeconomic status, to be foreign born, to have foreign-born parents, to have a non-intact family and to live in a Catholic canton. They were also more likely to have had their first intercourse in the context of a casual relationship, to have been intoxicated at the time and more likely to regret it. Participants in the contraceptive group reported a higher family socioeconomic status, had intact families, did not live in Catholic cantons, were older and in a steady relationship at first intercourse. CONCLUSION Contraception is generally used at first intercourse in Switzerland. Improvements can still be made concerning contraception use in the most vulnerable social strata such as low income families or foreign status.